Formulation, optimization, and characterization of snakehead fish (Ophiocephalus Striatus) powder nanoemulgel - Robert Tungadi; Prisca Wicita (Universidade de São Paulo, 2020)
The aim of the present study was to characterize and evaluate nanoemulgel of snakehead fish powder (SFP) for the poorly water-soluble drug. SFP was formulated into nanoemulsion utilizing the best comparison of surfactant, co-surfactant, and oil. Diverse nanoemulsion components (oil, surfactant, and co-surfactant) were chosen based on solvency and emulsification capacity. SFP 0.1% loaded nanoemulsion which tested by stress-stability testing which carried out for all formulations and those that passed these tests were characterized for droplet size, polydispersity index (PDI), zeta potential, pH, viscosity, and transmittance. After that, nanoemulsion was added with 1.5%, 2.0%, and 2.5% of HPMC in different concentrations and mixed until nanoemulgel form and evaluated for pH, viscosity, spreadability, and extrudability measurement. The results of this research showed that SF nanoemulsion produced clear, stable, and transparent formula having the transmittance value 99.87%. Mean droplet size and zeta potential of the optimized nanoemulsion (NE4) were found to be 98.6±0.93 nm (PDI 0.1±0.20) and -57.5±0.3 MV respectively. Meanwhile, the evaluation results of nanoemulgel (NEG) showed NEG1.5 gave pH 6.0, viscosity 210 cP, spreadability 5.8 g cm/s and extrudability 1.4 g/cm2. Otherwise, NEG2.0 and NEG2.5 had high viscosity and pH generating low spreading on the skin i.e. 3.9 g cm/s and 2.8 g cm/s respectively. The results of the evaluation and preparation stability test showed a good level of stability of NEG1.5 with the viscosity and pH by one way ANOVA which did not change significantly.